A numerical approach to infer terrestrial heat flux from shallow temperature profiles in remote northern regions. (June 2021) - Miranda, Mafalda M.; Velez Márquez, Maria Isabel; Raymond, Jasmin; Dezayes, Chrystel
Graphical abstract: Highlights: Heat flux evaluated numerically with a 1D inverse heat conduction problem. Time-varying upper boundary condition reproducing paleoclimate events. Temperature and pressure-dependent thermal conductivity considered in the model. Heat flux in the range 31.8 – 69.4 mW m −2 depending on paleoclimate and thermophysical properties conditions. Low-cost method to help advancing geothermal exploration in remote northern regions. Abstract: Assessing the geothermal potential in remote northern regions is challenging. First, due to remoteness and, second, due to data gaps. Often, Earth heat flux is inferred from deep equilibrium temperature profiles. However, in remote areas where deep boreholes are nonexistent, an adapted methodology is needed. Therefore, this study presents a new versatile and reliable numerical approach that simulates climate events and infers heat flux from a shallow temperature profile (80 m depth). Thus, addressing the challenge linked with heat flux assessment in northern regions and offering an original contribution to advance geothermal research in remote areas facing energy development challenges.